Vitamin D Binding Protein and Renal Injury in Acute Decompensated Heart Failure - Diaz-Riera, Elisa; García-Arguinzonis, Maisa; López, Laura; Garcia-Moll, Xavier; Badimon, Lina; Padró, Teresa (Frontiers in Cardiovascular Medicine, 2022)
Background Renal function in acute decompensated heart faiulre (ADHF) is a strong predictor of disease evolution and poor outcome. Current biomarkers for early diagnostic of renal injury in the setting of ADHF are still controversial, and their association to early pathological changes needs to be established. By applying a proteomic approach, we aimed to identify early changes in the differential urine protein signature associated with development of renal injury in patients hospitalised due to ADHF. Materials and Methods Patients (71 [64–77] years old) admitted at the emergency room with ADHF and hospitalised were investigated (N = 64). Samples (urine/serum) were collected at hospital admission (day 0) and 72 h later (day 3). Differential serum proteome was analysed by two-dimensional electrophoresis and matrix-assisted laser desorption/ionisation-time of flight (MALDI-ToF/ToF). Validation studies were performed using ELISA. Results Proteomic analysis depicted urinary vitamin D binding protein (uVDBP) as a two spots protein with increased intensity in ADHF and significant differences depending on the glomerular filtration rate (GFR). Urinary VDBP in patients with ADHF at hospitalisation was > threefold higher than in healthy subjects, with the highest levels in those patients with ADHF already presenting renal dysfunction. At day 3, urine VDBP levels in patients maintaining normal renal function dropped to normal values (P = 0.03 vs. day 0). In contrast, urine VDBP levels remained elevated in the group developing renal injury, with values twofold above the normal range (P < 0.05), while serum creatinine and GF levels were within the physiological range in this group. Urinary VDBP in ADHF positively correlated with markers of renal injury such as cystatin C and Kidney Injury Molecule 1 (KIM-1). By ROC analysis, urinary VDBP, when added to cystatin C and KIM-1, improved the prediction of renal injury in patients with ADHF. Conclusion We showed increased urine VDBP in patients with ADHF at hospital admission and a differential uVDBP evolution pattern at early stage of renal dysfunction, before pathological worsening of GFR is evidenced.